Healthcare service use patterns among autistic adults: A systematic review with narrative synthesis. (February 2022) - Gilmore, Daniel; Krantz, Morgan; Weaver, Lindy; Hand, Brittany N
Autistic adults often experience barriers to healthcare that can cause their healthcare service use to be unique from other populations. We conducted a systematic review to gather the most recent evidence about how often autistic adults use five important healthcare services (the emergency department, hospitalization, outpatient mental health, preventive services, and primary care) compared to populations of non-autistic adults. We searched six electronic research databases for articles. Our search strategy identified N = 2964 unique articles. Ultimately, we included N = 16 articles in our review. Most included studies (N = 13) were high-quality level 3a studies that compared autistic adults' service use to a non-autistic population comparison group (N = 11), and examined emergency department use (N = 12). Autistic adults most often had equal or higher use of services than population comparison groups across all healthcare services we examined. Although autistic adults had greater use of primary care and preventive services than comparison groups, frequent emergency department visits and hospitalizations may reflect that these services are not adequately meeting autistic adults' needs. Future research should identify targets for improving autistic adults' access to and use of primary care and preventive services, which may ultimately reduce frequent use of the emergency department and hospitalizations. Lay abstract: Autistic adults often have complex healthcare needs due to factors like having other health conditions, sensory sensitivities, and limited access to healthcare providers who are trained to provide care for them. All these factors may influence the healthcare services that autistic adults use. In this review, we searched six electronic research databases to gather the most recent evidence about how often autistic adults use five important healthcare services (the emergency department, hospitalization, outpatient mental health, preventive services, and primary care) compared to populations of non-autistic adults. A total of 16 articles were ultimately included in this review. Most articles found that autistic adults had equal or higher use of healthcare services than non-autistic adults. Autistic adults frequently used the emergency department and hospital. This may indicate that routine outpatient care in the community is not meeting their needs. Our findings show the importance of improving care at this level for autistic adults to reduce overuse of the emergency department (in this article referred to as ED) and hospital.